Pengaruh Servicescape Terhadap Kepuasan Konsumen di Workas Coffee Kota Padang - Ruziano, Kevin; Surenda, Rian; Azwar, Hendri (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2024)
This research originated from the existence of servicescape problems towards visitors that can affect customer satisfaction. The purpose of this study was to measure the effect of servicescape on consumer satisfaction at Workas Coffee Padang. This type of research is quantitative using a causal associative approach. The research variable is the independent variable (servicescape) and the dependent variable (Customer Satisfaction). The population is consumers who come to workas coffee padang. The number of respondents to the study was 92 people obtained by using non-probability sampling technique. The types of data are primary data and secondary data. Data collection by indirect communication or distributing questionnaires. The instrument is a questionnaire (questionnaire) arranged according to a Likert scale. Test the instrument by means of validity and reliability tests. Data were analyzed with basic statistics on research results and data descriptions. Test requirements analysis using the normality test, homogeneity test and linearity test. The result is that the servicescape category is quite good with a percentage of 60.54%, consumer satisfaction is in the fairly good category with a percentage of 63.47%, the R Square value is 0.135, with sig. 0.016 <0.05, meaning that the effect of servicescape on customer satisfaction is 13.5%. while 86.5% is influenced by other factors that have not been studied in this study.